1995
DOI: 10.1002/jat.2550150509
|View full text |Cite
|
Sign up to set email alerts
|

Effects of copper on gill structure and transport function in the rainbow trout, oncorhynchus mykiss

Abstract: Effects of copper were studied in freshwater adapted rainbow trout using the perfused head preparation. In its monovalent chemical form, copper at millimolar concentrations had no significant effects on Na+ and water transport. By contrast, the divalent form produced an increase in gill perfusion pressure, a significant reduction in Na+ influx and water fluxes and reversed Na+ net flux. Observations by light microscopy showed important cell damage (oedema, mucus production, cellular desquamation). By electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(19 citation statements)
references
References 29 publications
(2 reference statements)
2
14
0
3
Order By: Relevance
“…Some studies revealed that interstitial edema is one of the more frequent lesions observed in gill epithelium of fish exposed to heavy metals (Mallatt 1985). The results of this study confirm the occurrence of edema independently of copper levels, as in other fish species (Sola et al 1995, Bury et al 1998. The lifting of lamellar epithelium is other histological change observed, probably induced by the incidence of severe edema (Arellano et al 1999, Pane et al 2004, Schwaiger et al 2004.…”
Section: Discus Discus Discus Discus Discussion Sion Sion Sion Sionsupporting
confidence: 85%
“…Some studies revealed that interstitial edema is one of the more frequent lesions observed in gill epithelium of fish exposed to heavy metals (Mallatt 1985). The results of this study confirm the occurrence of edema independently of copper levels, as in other fish species (Sola et al 1995, Bury et al 1998. The lifting of lamellar epithelium is other histological change observed, probably induced by the incidence of severe edema (Arellano et al 1999, Pane et al 2004, Schwaiger et al 2004.…”
Section: Discus Discus Discus Discus Discussion Sion Sion Sion Sionsupporting
confidence: 85%
“…Lamellar epithelial lifting, hyperplasia, and lamellar fusion are nonspecific responses that are known to be induced by many gill tissue irritants (Mallatt, 1985). However, focal points of cellular hypertrophy and necrosis followed by epithelial rupture reflect the direct deleterious effects of heavy metals in fish gills (Mallatt, 1985;Sola et al, 1995). All these lesions may impair respiratory function.…”
Section: Discussionmentioning
confidence: 99%
“…One of the ways that waterborne Cu causes ionoregulatory disturbances in fish is via non-competitive inhibition of branchial Na + /K + -ATPase activity (Laurén and McDonald, 1987a;Sola et al, 1995;Pelgrom et al, 1995;Li et al, 1998). Intracellular Cu competes with Mg 2+ for binding sites on the ATP molecule and forms a physiologically inert ATP complex, Cu-ATP (Li et al, 1996).…”
Section: Discussionmentioning
confidence: 99%